The taxonomic resurrection of Muscari haradjianii (Asparagaceae, Scilloideae), and a new synonym in the genus Muscari in Turkey - Eroğlu, Hüseyi̇n; Pinar, Süleyman Mesut (Phytotaxa, 2019)
The taxonomical status of Muscari haradjianii from Turkey was reevaluated in this study. We provide here a detailed morphological description, including pollen and seed features, distribution range, and chromosome number. There has been frequent confusion regarding the differences between M. haradjianii and its congeners M. longipes and M. tenuiflorum. Here, we clarify the differences among these species. In addition, it was determined that M. ufukii is a synonym for M. haradjianii.